Enabling the web of things: facilitating deployment, discovery and resource access to IoT objects using embedded web services. (1st January 2014) - Ishaq, Isam; Hoebeke, Jeroen; Rossey, Jen; De Poorter, Eli; Moerman, Ingrid; Demeester, Piet
Today, the IETF Constrained Application Protocol (CoAP) is being standardised. CoAP takes the internet of things to the next level: it enables the implementation of RESTful web services on embedded devices, thus enabling the construction of an easily accessible web of things. However, before tiny objects can make themselves available through embedded web services, several manual configuration steps are still needed to integrate a sensor network within an existing networking environment. In this paper, we describe a novel selforganisation solution to facilitate the deployment of constrained networks and enable the discovery, end-to-end connectivity and service usage of these newly deployed sensor nodes. By using embedded web service technology, the need of other protocols on these resource constrained devices is avoided. It allows automatic hierarchical discovery of CoAP servers, resulting in a browsable hierarchy of CoAP servers, which can be accessed both over CoAP and hypertext transfer protocol.